An initial study of the in-service training programs for the faculty of St. Joseph's Academy, school year 1976-77: An evaluation and teachers' preferences survey - Orbase, Fe Q. (Animo Repository, 1977)
v. 1. The study looks into the status of the in-service training programs of St. Joseph's Academy (SJA) during the school year 1976-1977 and to survey the professional growth needs of the faculty in the same school. The descriptive-survey method of research was used in the study. The criteria for evaluation were based on the goals, principles and guidelines formulated by Filipino and foreign education experts. Findings from masteral studies made on the same subject were also utilized as guides in the construction of questionnaires which was the evaluation instrument. The respondents were the religious and lay faculty members of SJA numbering 22 and representing 92% of the entire faculty. The study concluded that on the basis of educational qualifications, more than three-fourths of the faculty were obviously inadequate to cope up with increasing needs of the students. Therefore, the faculty needed more in-service training activities to strengthen their minimum educational qualifications. On the basis of the years of teaching experience, more than one-half of the lay faculty had spent one to five years teaching in SJA. Because of the length of their teaching experience in the school, majority of them had possibly not acquired fully the necessary social and professional competencies in service. Therefore, the faculty needed more growth opportunities. On the basis of the positive responses to the evaluation criteria, the strengths of the in-service training programs of the school during the school year 1976-77 appeared to be the development of the teacher's personality, development of skills in speaking, listening and problem-solving, programs organized around the felt needs of the faculty, the program atmosphere conducive to freedom of expression, administrators' moral support seemed to be the principal motivating factor in the accomplishment of the program, and every activity was concluded by an evaluation. The apparent weaknesses of the in-service training include improvement of instruction which seemed to have v. 2. This project presents vital statements to be reflected in a faculty handbook in order to answer the questions and problems of teachers relative to the treatment of their individual rights as teachers and employees of St. Joseph Academy (SJA). The study made use of the descriptive method of research. The situation and existing conditions at SJA were described as observed and experienced personally by the writer. Sources of data also include the relevant records and publications of SJA faculty manuals from other schools project studies made on the subject provisions from the Labor Code of the Philippines the Manual of Regulations for Private Schools the Magna Carta for Public School Teachers and documents from the Department of Education and Culture. The proposed handbook presented statements of the institutional philosophy educational objectives position descriptions which defined the functions, duties, organizational relationships and qualifications of the various administrative officials, faculty and staff and the essential policies, procedures, rules and regulations on service conditions and evaluation of teacher performance and behavior. v. 3. This financial and behavioral problem arises out of poor application of managerial principles in the planning aspects, particularly those that affect personnel welfare. Majority of the teaching staff of the Our Lady of Mercy (OLM) School, agreed to file a complaint against the School with the Department of Labor, resulting from a small allocation of increment for a teaching load perceived as heavier than the previous year no provision for a 13th-month pay and emergency allowances in the salary agreement and an absence of clearly-defined set of salary policies for the teaching personnel. The following possible courses of action were presented : 1. Revision of the application for increase in tuition and/or other school fees on the part of the Administration in order to ensure the increase of fees applied for. 2. Presentation of the school financial status of the preceding year to the faculty, since a re-application for increase in school fees could not be made at the beginning of the coming school year. 3. Faculty could have expressed their complaints prior to signing their assignment papers in order that standing decisions could have been reconsidered before classes started. Consequences of the abovementioned courses of action were given by the author.